Range of Motion and Muscle Stiffness Differences in Junior Tennis Players with and without a History of Shoulder Pain - Joshua Colomar; Javier Peña; Jordi Vicens-Bordas; Ernest Baiget (International Journal of Sports Physical Therapy)
# Background